Sistem Rekomendasi dan Peminjaman Buku Menggunakan Algoritma Hybrid Based Filtering - Lily Aprilyani; Ransi, Natalis; Saputra, Rizal Adi; Isnawaty, Isnawaty (SISFOTENIKA, 2024)
SMAN 1 Ladongi in East Kolaka has gained a reputation as an educational institution that is highly committed in providing quality education for the younger generation. SMA Negeri 1 Ladongi in East Kolaka Regency has a diverse collection of books, but the library service is still done manually. This process is not only time-consuming, but also less efficient, especially considering the large number of book collections. Implementing an online book recommendation and lending system can be a solution to improve the effectiveness and efficiency of library services. With a mobile web-based system, students and library staff can easily access book recommendations and perform the loan process online. This research uses a Hybrid Recommendation System that combines Item-Based Collaborative Filtering and User-Based Collaborative Filtering methods. The combination of these two methods aims to obtain better recommendation results. Based on the results of testing the accuracy of the recommendations that have been carried out, it is obtained for the MAE value of 4.52, then the MSE value is 0.02 and for the MAPE value obtained is 0.76%.